A dialogue with the 'self': Identity exploration processes in intergroup dialogue for Jewish students in Israel. (June 2017) - Shamoa-Nir, Lipaz
Abstract: Intergroup dialogues can create a safe environment that encourages individuals to engage in self reflection. This article has examined identity exploration processes among undergraduate students who have participated in a dialogue course. Findings have pointed out several factors that have enabled self-exploration in the group and the dialogue course was fulfilling for most students. The participants felt that the dialogue had helped them form a greater understanding of their identities through two levels of discourse: with the 'self' and with 'the other' - however, findings also indicated a process that appears to disrupt a 'deep' and authentic discourse and can be considered as a contestation of identity. The contribution of this research lies in investigating how identities are shaped within a context of intergroup dialogues and in proposing several hypotheses and questions to advance the research in this field.